An HPLC method for soy isoflavone extracts quantification using internal standard methodology - Turco, M. D. (2019)
Fil: Turco, M. D. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.